Comparison of serum homocysteine level in young and middle-aged adult patients with coronary artery disease: Homocysteine in coronary artery disease (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Deaths due to coronary artery disease have been increasing in young people aged